PENGARUH KETERLIBATAN KERJA, BEBAN KERJA DAN KONFLIK PERAN TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI PADA DINAS PENDIDIKAN ACEH - Ferri Alfian; Muhammad Adam; Mahdani Ibrahim (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACT The purpose of this study was to determine: (1) describe the work engagement, workload, role conflict, job satisfaction and employee performance (2) the influence of job satisfaction on employee performance, (3) the magnitude of the effect of workload on job satisfaction (4) the amount of the effect of role conflict on job satisfaction of employees (5) the effect of work engagement to employee performance, (6) the effect of workload on employee performance (7) the effect of role conflict on employee performance, and (8) the effect of job satisfaction on employee performance. As for the object of this study is the involvement of work, workload, role conflict, job satisfaction and employee performance. The results showed that (1) the involvement of work, workload, role conflict, job satisfaction and employee performance Department of Education Aceh has been running well, because the obtained mean value is greater than the average value of hope, (2) job involvement positive and significant effect on the employee satisfaction, (3) there are significant workload on employee satisfaction, (4) conflict of roles affect the job satisfaction of employees, (5) the involvement of influential work on employee performance, (6) the workload positive and significant effect on employee performance, (7) the results of research on the role conflicts prove that role conflict and significant positive effect on employee performance, and (8) the results of the study also show that employee satisfaction and significant positive effect on employee performance Department of Education Aceh. Keywords Work Engagement, Work Load, Role Conflict, Job Satisfaction and Employee Performance